- Calculators
- ::
- Polynomial Calculators
- ::
- Polynomial Roots Calculator

**This free math tool finds the roots (zeros) of a given polynomial.**
The calculator computes exact solutions for quadratic, cubic, and quartic equations.

It also displays the step-by-step solution with a detailed explanation.

**problem**

Find roots of polynomial $$ p(x) = 2x^2+3x-14 $$

**solution**

The roots of polynomial $ p(x) $ are:

$$ \begin{aligned}x_1 &= 2\\[1 em]x_2 &= -\frac{ 7 }{ 2 } \end{aligned} $$**explanation**

The solutions of $ 2x^2+3x-14 = 0 $ are: $ x = -\dfrac{ 7 }{ 2 } ~ \text{and} ~ x = 2$.

You can use step-by-step quadratic equation solver to see a detailed explanation on how to solve this quadratic equation.

working...

EXAMPLES

example 1:ex 1:

find roots of the polynomial $4x^2 - 10x + 4$

example 2:ex 2:

find polynomial roots $-2x^4 - x^3 + 189$

example 3:ex 3:

solve equation $6x^3 - 25x^2 + 2x + 8 = 0$

example 4:ex 4:

find polynomial roots $2x^3-x^2-x-3$

example 5:ex 5:

find roots $2x^5-x^4-14x^3-6x^2+24x+40$

Search our database of more than 200 calculators

TUTORIAL

The process of finding polynomial roots depends on its **degree**. The degree is the largest exponent in the polynomial. For example,
the degree of polynomial $ p(x) = 8x^\color{red}{2} + 3x -1 $ is $\color{red}{2}$.

We name polynomials according to their degree. For us, the most interesting ones are:
**quadratic** - degree 2, **Cubic** - degree 3, and **Quartic** - degree 4.

This is the standard form of a quadratic equation

$$ a\,x^2 + b\,x + c = 0 $$The formula for the roots is

$$ x_1, x_2 = \dfrac{-b \pm \sqrt{b^2-4ac}}{2a} $$**Example 01: **Solve the equation $ 2x^2 + 3x - 14 = 0 $

In this case we have $ a = 2, b = 3 , c = -14 $, so the roots are:

$$ \begin{aligned} x_1, x_2 &= \dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\ x_1, x_2 &= \dfrac{-3 \pm \sqrt{3^2-4 \cdot 2 \cdot (-14)}}{2\cdot2} \\ x_1, x_2 &= \dfrac{-3 \pm \sqrt{9 + 4 \cdot 2 \cdot 14}}{4} \\ x_1, x_2 &= \dfrac{-3 \pm \sqrt{121}}{4} \\ x_1, x_2 &= \dfrac{-3 \pm 11}{4} \\ x_1 &= \dfrac{-3 + 11}{4} = \dfrac{8}{4} = 2 \\ x_2 &= \dfrac{-3 - 11}{4} = \dfrac{-14}{4} = -\dfrac{7}{2} \end{aligned} $$Sometimes, it is much easier not to use a formula for finding the roots of a quadratic equation.

**Example 02:** Solve the equation $ 2x^2 + 3x = 0 $

Because our equation now only has two terms, we can apply **factoring**.
Using factoring we can reduce an original equation to two simple equations.

**Example 03:** Solve equation $ 2x^2 - 10 = 0 $

This is also a quadratic equation that can be solved without using a quadratic formula.

. $$ \begin{aligned} 2x^2 - 18 &= 0 \\ 2x^2 &= 18 \\ x^2 &= 9 \\ \end{aligned} $$The last equation actually has two solutions. The first one is obvious

$$ \color{blue}{x_1 = \sqrt{9} = 3} $$and the second one is

$$ \color{blue}{x_2 = -\sqrt{9} = -3 }$$To solve a cubic equation, the best strategy is to guess one of three roots.

**Example 04:** Solve the equation $ 2x^3 - 4x^2 - 3x + 6 = 0 $.

**Step 1:** Guess one root.

The good candidates for solutions are factors of the last coefficient in the equation. In this example, the last number is -6 so our guesses are

1, 2, 3, 6, -1, -2, -3 and -6

if we plug in $ \color{blue}{x = 2} $ into the equation we get,

$$ 2 \cdot \color{blue}{2}^3 - 4 \cdot \color{blue}{2}^2 - 3 \cdot \color{blue}{2} + 6 = 2 \cdot 8 - 4 \cdot 4 - 6 - 6 = 0$$So, $ \color{blue}{x = 2} $ is the root of the equation. Now we have to divide polynomial with $ \color{red}{x - \text{ROOT}} $

In this case we divide $ 2x^3 - x^2 - 3x - 6 $ by $ \color{red}{x - 2}$.

$$ ( 2x^3 - 4x^2 - 3x + 6 ) \div (x - 2) = 2x^2 - 3 $$Now we use $ 2x^2 - 3 $ to find remaining roots

$$ \begin{aligned} 2x^2 - 3 &= 0 \\ 2x^2 &= 3 \\ x^2 &= \frac{3}{2} \\ x_1 & = \sqrt{ \frac{3}{2} } = \frac{\sqrt{6}}{2}\\ x_2 & = -\sqrt{ \frac{3}{2} } = - \frac{\sqrt{6}}{2} \end{aligned} $$To solve cubic equations, we usually use the factoting method:

**Example 05:** Solve equation $ 2x^3 - 4x^2 - 3x + 6 = 0 $.

Notice that a cubic polynomial has four terms, and the most common factoring method for such polynomials is factoring by grouping.

$$ \begin{aligned} 2x^3 - 4x^2 - 3x + 6 &= \color{blue}{2x^3-4x^2} \color{red}{-3x + 6} = \\ &= \color{blue}{2x^2(x-2)} \color{red}{-3(x-2)} = \\ &= (x-2)(2x^2 - 3) \end{aligned} $$Now we can split our equation into two, which are much easier to solve. The first one is $ x - 2 = 0 $ with a solution $ x = 2 $, and the second one is $ 2x^2 - 3 = 0 $.

$$ \begin{aligned} 2x^2 - 3 &= 0 \\ x^2 = \frac{3}{2} \\ x_1x_2 = \pm \sqrt{\frac{3}{2}} \end{aligned} $$** Please tell me how can I make this better.**

436 090 367 solved problems